2017
DOI: 10.1021/acs.jpcc.6b11329
|View full text |Cite
|
Sign up to set email alerts
|

DFT Global Optimization of Gas-Phase Subnanometer Ru–Pt Clusters

Abstract: The global optimization of subnanometer Ru–Pt binary nanoalloys in the size range 2–8 atoms is systematically investigated using the Birmingham Parallel Genetic Algorithm (BPGA). The effect of size and composition on the structures, stabilities and mixing properties of Ru–Pt nanoalloys are discussed. The results revealed that the maximum mixing tendency is achieved for 40–50% Ru compositions. Global minimum structures show that the Ru atoms prefer to occupy central and core positions and maximize coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 52 publications
10
23
0
Order By: Relevance
“…Higher binding energy indicates higher stability. As expected, due to the increase in the average number of metal-metal bonds, the binding energy generally increases with increasing cluster size, as previously reported for different metallic systems [70,71,93,94]. Pure Au clusters are relatively less stable (having lower Eb values) than pure Cu clusters of the same size.…”
Section: Energetic Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Higher binding energy indicates higher stability. As expected, due to the increase in the average number of metal-metal bonds, the binding energy generally increases with increasing cluster size, as previously reported for different metallic systems [70,71,93,94]. Pure Au clusters are relatively less stable (having lower Eb values) than pure Cu clusters of the same size.…”
Section: Energetic Analysissupporting
confidence: 86%
“…All of the ΔHL plots show marked odd-even alternations, with larger ΔHL values for even-atom (and, hence, even-electron) clusters and smaller values for odd-atom (odd-electron) clusters. This behaviour has previously been explained in terms of the electronic shell model [93][94][95][96][97][98][99]. For the free pure and mono-substituted clusters, N=6 and N=8 tend to have the highest ΔHL values, which is consistent with the ∆2E plots, since high HOMO-LUMO gaps typically correlate with low total electronic energy (stabilisation of filled orbitals).…”
Section: Energetic Analysissupporting
confidence: 79%
“…The BE for binary and ternary clusters (Song et al, 2005; Demiroglu et al, 2017) is given by Equations (3) and (4):…”
Section: Theoretical Approachmentioning
confidence: 99%
“…It was recently shown that alloying ruthenium-oxide with chromium could improve stability and activity of the catalyst in acidic media [51]. Computational work by Demiroglou et al predicted that alloying with platinum increases the ruthenium cluster's stability [52]. A systematic experimental investigation of the effect of doping or alloying ruthenium/ ruthenium oxide clusters is still lacking.…”
Section: Model Systems For Oer Catalysts In Acidic Mediamentioning
confidence: 99%